The Crosstalk Between Liver Sinusoidal Endothelial Cells and Hepatic Microenvironment in NASH Related Liver Fibrosis - Du, Wei; Wang, Lin (Frontiers in Immunology, 2022)
Chronic liver injury can be caused by many factors, including virus infection, alcohol intake, cholestasis and abnormal fat accumulation. Nonalcoholic steatohepatitis (NASH) has become the main cause of liver fibrosis worldwide. Recently, more and more evidences show that hepatic microenvironment is involved in the pathophysiological process of liver fibrosis induced by NASH. Hepatic microenvironment consists of various types of cells and intercellular crosstalk among different cells in the liver sinusoids. Liver sinusoidal endothelial cells (LSECs), as the gatekeeper of liver microenvironment, play an irreplaceable role in the homeostasis and alterations of liver microenvironment. Many recent studies have reported that during the progression of NASH to liver fibrosis, LSECs are involved in various stages mediated by a series of mechanisms. Therefore, here we review the key role of crosstalk between LSECs and hepatic microenvironment in the progression of NASH to liver fibrosis (steatosis, inflammation, and fibrosis), as well as promising therapeutic strategies targeting LSECs.